Reorientasi Filosofis Dalam Perencanaan Pendidikan Islam - Sabrifha, Eli; Assyafar, Yudistira (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
Islamic education planning often becomes trapped in technical-administrative dimensions and bureaucratic routines, losing its philosophical essence as an instrument for molding insan kamil (the perfect human). This article aims to reformulate (reorient) the philosophical foundations of Islamic education planning to effectively address modern challenges without compromising its spiritual identity. This research employs a qualitative method with a library research approach and descriptive-philosophical analysis. The findings indicate that philosophical reorientation must commence by integrating tawhidic values as an epistemological basis at every stage of planning, encompassing curriculum, human resources, and institutional management. Planning should not merely be oriented toward fulfilling labor market demands (pragmatism) but must be balanced with an ukhrawi (hereafter) orientation and the cultivation of adab (character/ethics). The conclusion of this article emphasizes that visionary Islamic education planning is characterized by its ability to synergize intellectual proficiency, technological advancement, and spiritual stability through a paradigm shift from mechanistic planning toward organic-transcendental planning.